2015
DOI: 10.1071/fp14025
|View full text |Cite
|
Sign up to set email alerts
|

How different pruning severities alter shoot structure: a modelling approach in young ‘Nonpareil’ almond trees

Abstract: Axillary meristem fate patterns along shoots, also referred to as shoot structure, appear to be fairly consistent among trees within a genotype growing under similar conditions. Less is known about shoot structural plasticity following external manipulations, such as pruning. The aim of this study on almond (Prunus dulcis (Mill.)) shoots was to investigate how pruning severity affects the structure of 1-year-old shoots that grew after pruning (regrowth shoots), the 2-year-old portion of shoots that remained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These methods analyze tree architecture as a succession of zones with a different proportion of node types whose arrangement is defined by transition probabilities, using branches as the study subject [16,[21][22][23]. This approach has been applied to almond under different circumstances [24][25][26]. Although these models are useful for describing and visualizing repetitive patterns in tree architecture and branching formation, they are difficult to incorporate into genomic analyses, such as genome-wide association studies (GWAS).…”
Section: Introductionmentioning
confidence: 99%
“…These methods analyze tree architecture as a succession of zones with a different proportion of node types whose arrangement is defined by transition probabilities, using branches as the study subject [16,[21][22][23]. This approach has been applied to almond under different circumstances [24][25][26]. Although these models are useful for describing and visualizing repetitive patterns in tree architecture and branching formation, they are difficult to incorporate into genomic analyses, such as genome-wide association studies (GWAS).…”
Section: Introductionmentioning
confidence: 99%
“…In plantation P2, the RLs of 52 metabolites in UPTTs were lower than in PTTs (VIP > 1, FC < 0.66, and P < 0.05), and the majority of these metabolites were flavonoids (28), followed by phenolic acids (8) organic acids (4) and nucleotides and derivatives (3), including kaempferin, cynaroside, quercitrin, phloretin, and isovitexin. In addition, the RLs of 58 metabolites in UPTTs were higher than in PTTs, and the majority of these metabolites were flavonoids (17), lipids (15) and phenolic acids (15), followed by lignans and coumarins (5) and tannins (3 metabolites), including tyramine, quillaic acid, kaempferitrin, coumarin, rutin and naringenin (VIP > 1, FC > 1.5, and P < 0.05) (Figure 5B). The high levels of serine and phenylalanine in UPTTs were in accordance with HPLC measurements.…”
Section: The Differences In Metabolitesmentioning
confidence: 99%
“…(14), tannins (10), and terpenoids (2). They were further grouped into 30 sub-classes, including flavonols (34), free fatty acids (28), saccharides and alcohols (20), flavanols (18), flavonoid carbonoside (17), Lysophosphatidylcholine (15), proanthocyanidins (14), anthocyanins (9), and isoflavones (4).…”
Section: The Differences In Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Negrón et al [13] reported that the pattern of shoot production and fruiting was determined by cultivar genotype. The formation of proleptic and sylleptic shoots has also been analyzed under different environments or experimental treatments, for example, water deficiency or pruning [14,15]. In peach (P. persica (L.) Batsch), it has been reported that more floral buds are produced on proleptic than sylleptic shoots [16].…”
Section: Introductionmentioning
confidence: 99%